Hypothalamic–Pituitary–Gonadal Axis Involvement in Learning and Memory and Alzheimer’s Disease: More than “Just” Estrogen - Blair, Jeffrey A.; McGee, Henry; Bhatta, Sabina; Palm, Russell; Casadesus, Gemma (Frontiers in Endocrinology, 2015)
Accumulating studies affirm the effects of age-related endocrine dysfunction on cognitive decline and increasing risk of neurodegenerative diseases. It is well known that estrogen can be protective for cognitive function, and more recently testosterone and luteinizing hormone have also been shown to modulate learning and memory. Understanding the mechanisms underlying hypothalamic-pituitary-gonadal axis associated cognitive dysfunction is crucial for therapeutic advancement. Here, we emphasize that reproductive hormones are influential in maintaining neuronal health and enhancing signaling cascades that lead to cognitive impairment. We summarize and critically evaluate age-related changes in the endocrine system, their implications in the development of Alzheimer’s disease, and the therapeutic potential of endocrine modulation in the prevention of age-related cognitive decline.